Detection of inguinal lymph nodes is promising for the diagnosis of periprosthetic joint infection - Qin, Leilei; Zhao, Chen; Wang, Hai; Yang, Jianye; Chen, Li; Su, Xudong; Wei, Li; Zhang, Tao; Li, Jia; Jian, Changchun; Hu, Ning; Huang, Wei (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Localized inguinal lymphadenopathy often represents lower extremity pathogen infection, while normalized lymphadenopathy is associated with infection regression. We hypothesized that inguinal lymph nodes (LNs) were enlarged in Periprosthetic Joint Infection (PJI) patients and that normalized inguinal LNs would be a promising way to determine the timing of reimplantation. Methods: We prospectively enrolled 176 patients undergoing primary and revision hip or knee arthroplasty. All patients underwent ultrasound examination of inguinal LNs preoperatively. The diagnostic value of inguinal LNs in PJI was evaluated by the receiver operating characteristic (ROC) curve. Results: The median level of inguinal LNs was 26mm in the revision for PJI group compared with 12 mm in the aseptic revision group (p< 0.0001). The size of the inguinal LNs well distinguishes PJI from aseptic failure (AUC= 0.978) compare with ESR (AUC= 0.707) and CRP (AUC= 0.760). A size of 19mm was determined as the optimal threshold value of the inguinal LNs for the diagnosis of PJI, with a sensitivity of 92% and specificity of 96%. Conclusions: Ultrasonic analysis of inguinal LNs is a valuable piece of evidence for the diagnosis of PJI and evaluation of persistent infection.